Maternally Instigated Diapause in Aedes albopictus: Coordinating Experience and Internal State for Survival in Variable Environments - Lee, In Hae; Duvall, Laura B. (Frontiers in Behavioral Neuroscience, 2022)
The Asian tiger mosquito, Aedes albopictus, is one of the most dangerous invasive species in the world. Females bite hosts, including humans, to obtain blood for egg development. The ancestral range likely spanned from India to Japan and this species has invaded a substantial portion of the globe. Ae. albopictus can be categorized into temperate and tropical populations. Females living in temperate regions respond to cues that predict unfavorable environmental conditions by producing eggs that enter maternally-instigated embryonic diapause, a developmentally arrested state, which protects the embryos until favorable conditions return. Females must integrate environmental cues and internal physiological state (blood feeding and reproductive status) to allocate nutrients and regulate reproduction. Between interfertile tropical and temperate populations there is variation in responses to environmental cues depending on whether females are actively producing diapause versus non-diapause eggs and whether they originate from populations that lack diapause. Although diapause-inducing environmental cues and diapause eggs have been extensively characterized, little is known about how females detect gradual environmental changes and coordinate reproduction with season to maximize offspring survival. Previous studies suggest that the circadian system is detects daylength as a critical cue. However, it is unknown which clock components are important, how these connect to reproductive physiology, and how they differ between behavioral states or across populations with variable diapause competence. We showcase Ae. albopictus as an emerging species for neurogenetics to study how the nervous system combines environment and internal state to optimize reproduction. We review environmental cues for diapause induction, downstream pathways that control female metabolic changes and reproductive capacity, and diapause heterogeneity between populations with different evolutionary histories. We highlight genetic tools that can be implemented in Ae. albopictus to identify signaling molecules and circuits that control diapause. The tools and discoveries made in this species could translate to a broader understanding of how environmental cues are interpreted to alter reproductive physiology in other species and how populations with similar genetic and circuit organizations diversify behavioral patterns. These approaches may yield new targets to disrupt mosquito reproductive capacity, which could be exploited to reduce mosquito populations and pathogens they transmit.